A new method for studying the halo effect in teachers' judgement and its antecedents: Bringing out the role of certainty. (12th November 2020) - Sanrey, Camille; Bressoux, Pascal; Lima, Laurent; Pansu, Pascal
Abstract : Background: In academic contexts, teachers' judgements are central to instruction and have many consequences for students' self‐perceptions. Understanding the cognitive biases that may exist in teachers' judgements is thus of central importance. Aims: This paper presents two studies in which we aimed to investigate the presence of a halo effect in teachers' judgements (Study 1 and Study 2) and to clarify the conditions for the emergence of this halo effect by analysing the influence of judgement certainty (Study 2). A major contribution of these studies was to provide a new measure of the halo effect in order to achieve these goals. Sample(s): In the first study, 25 teachers and their 199 students were asked to complete the measures, while the second study sample was composed of 20 teachers and their 180 students. Method: To analyse the presence of the halo effect in teachers' judgements in the two studies, scholastic achievement was measured using various standardized French language tests. Teachers were asked to indicate, for each of their students, whether they thought the student would answer correctly or incorrectly for each item on the standardized tests. In Study 2, to analyse the influence of judgement certainty, the teachers were asked to indicate after each item how certain they were about their response. Results and discussion: The results of both studies revealed the presence of a halo effect in teachers' judgements for each measure used (i.e., comparison of correlations, factorial analyses, and the new measure comparing variance scores), as the teachers' judgements were more homogeneous than the students' actual achievement levels. Furthermore, using the new measure, the second study revealed that high judgement certainty resulted in a stronger halo effect.